Riley farm-rhymes - Riley, James Whitcomb, 1849-1916 (Library of Indiana classics., 2013)
First published in 1883, this book includes many of James Whitcomb Riley's signature poems, including "Thoughts fer the Discuraged Farmer" and "When the Frost Is on the Punkin." Also graced by noted Brown County artist Will Vawter's folksy illustrations of farm scenes from our past, this Library of Indiana Classics edition faithfully reproduces the 1905 edition. This book offers a warm look at how farm life was depicted over a century ago.